HLA, Immune Response, and Susceptibility to COVID-19 - Tavasolian, Fataneh; Rashidi, Mohsen; Hatam, Gholam Reza; Jeddi, Marjan; Hosseini, Ahmad Zavaran; Mosawi, Sayed Hussain; Abdollahi, Elham; Inman, Robert D. (Frontiers in Immunology, 2021)
The contagious severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) that appeared in December 2019 has precipitated the global pandemic Coronavirus Disease 2019 (COVID-19) However, in many parts of African fewer than expected cases of COVID-19, with lower rates of mortality, have been reported. We suggest a theory regarding human leukocyte antigen (HLA) antigens and presentation of viral peptides which could be associated with susceptibility vs resistance to SARS-CoV-2 infections. Keywords: COVID-19, HLA antigens, Original Antigenic Sin